ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), PENGHAPUSAN AKTIVA PRODUKTIF KREDIT (PPAPK), CASH RATIO (CR), BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) DAN NET INTEREST MARGIN (NIM) TERHADAP PROFITABILITAS (ROA) BANK BUMN, BANK SWASTA NASIONAL, DAN BANK ASING DI INDONESIA TAHUN 2008-2017 - Whendi Denalta Pradani (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purpose of this studi are to determine how the effect of capital adequacy ratio (CAR), provision for loan losses (PPAPK), cash ratio (CR), operating expenses on operating income (BOPO), and net interest margin (NIM) to return on assets (ROA) banks in Indonesia and in state owned banks, foreign exchange commercial banks and foreign owned banks in Indonesia between 2008-2017. The model is estimated using panel data analysis where there are 4 models panel data consisting of : model 1 (all banks), model 2 (state owned banks), model 3 (foreign exchange commercial banks), and model 4 (foreign owned banks). The result showed that CAR, CR, BOPO, and NIM variable have significant effect on ROA for all models. Beside that the PPAPK variable have a positive effect for model 2 and model 4, while for model 1 and model 3 have a negative effect on ROA. Keywords : Bank Profitability, Financial Ratio, State Owned Banks, Foreign Exchange Commercial Banks and Foreign Owned Banks